The Influence of Benthik Traditional Gameson the Level of Sibling Rivalry among Children: A Quasi-Experimental Study - Adinda Putri Sholikhah; Abadina Ukhtisiwi; Lia Kurniawati; Anisya Salsabila Ainun Nur Azizah (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Abstract.Children's relationships with their siblings encompass a spectrum of experiences, ranging from positive connections to negative interactions. A notable negative facet that can emerge within sibling dynamics is the phenomenon of sibling rivalry. This phenomenon entails the manifestation of competition, jealousy, and animosity among siblings, often arising following the birth of a younger brother or sister.The prevalence of sibling rivalry is associated with adverse outcomes, including heightened anxiety and impaired emotional regulation in children. To address the intricate issue of sibling rivalry, fostering cooperative interactions among siblings has been proposed as a potential solution. This research aims to describe whether the modification of the traditional game "Benthik" from East Java can reduce siblingrivalry in children. Additionally, this study also elucidates how the concept of modifying the Benthik game can mitigate sibling rivalry in children. Employing a quasi-experimental methodology, the study was conducted at SD Negeri 1 Sumberjo, Bojonegoro, and involved 30 children aged 8 to 12, each of whom had at least one sibling. The paired sample t-test analysis results reveal a significant influence ofthe Benthik game on sibling rivalry conditions in children, with a p-value of 0.035 (<0.05) denoting statistical significance, thereby indicating that the modified Benthik game holds promise as an effective intervention for addressing sibling rivalry. In conclusion, the research contributes not only to the realm of addressing sibling dynamics but also to the preservation and utilization of traditional regional gamesamid the pervasive influence of digital engagement.